The diagnostic yield of CGH and WES in neurodevelopmental disorders - Alotibi, Raniah S.; Sannan, Naif S.; AlEissa, Mariam; Aldriwesh, Marwh G.; Al Tuwaijri, Abeer; Akiel, Maaged A.; Almutairi, Mashael; Alsamer, Alhanouf; Altharawi, Nouf; Aljawfan, Ghadah; Alotiabi, Badi; AlBlawi, Mohammed A.; et al. (Frontiers in Pediatrics, 2023)
Background Neurodevelopmental disorders are a group of conditions characterized by developmental delays leading to abnormal brain functions. The methods of diagnosis and treatment of these conditions are complicated, and their treatment involves a combination of various forms of therapy. In recent years, the development of high-resolution technologies has played an important role in revealing the microdeletions, microduplications, and single-nucleotide variants of the chromosomes and how they are linked to the development of neurodevelopmental disorders. The wide implementation and application of molecular methodologies have started to shed light on the functional importance of using the appropriate methods in detecting these genetic variations that are categorized as either pathogenic or benign. The study aimed to compare the diagnostic yield of comparative hybridization (CGH) and whole exome sequencing (WES) in neurodevelopmental disorders among children attending the King Abdullah Specialist Children Hospital, Riyadh, Saudi Arabia. Methods A retrospective study was conducted between 2015 and 2018 on 105 patients diagnosed with neurodevelopmental disorders through array-based CGH (Array-CGH) and WES. Results In a sample of 105 patients, 16% was the hit rate of copy number variations (CNVs). WES was requested for CNV-negative patients (n = 79), of which 30% was the hit rate of pathogenic or likely pathogenic single-nucleotide variants. There was a difference in the diagnostic yield between CGH (16%) and WES (30%). Conclusion WES was a better approach than Array-CGH to detect various DNA mutations or variants. Our findings could guide clinicians, researchers, and testing laboratories select the most cost-effective and appropriate approach for diagnosing their patients.